High Resolution Scanning Tunneling Microscopy of a 1D Coordination Polymer with Imidazole-Based N,N,O Ligands on HOPG - Fischer, Nina V.; Mitra, Utpal; Warnick, Karl-Georg; Dremov, Viatcheslav; Stocker, Michael; Wölfle, Thorsten; Hieringer, Wolfgang; Heinemann, Frank Wilhelm; Burzlaff, Nicolai; Görling, Andreas; Müller, Paul (Chemistry - A European Journal, 2014)
Novel k(3)-N,N,O ligands tend to form 1D coordination polymer strands. Deposition of 1D structures on highly oriented pyrolytic graphite (HOPG) was achieved from diluted solutions and polymer strands have been studied on HOPG by AFM/STM. Single strands were mapped by STM and their electronic properties were subsequently characterized by current imaging tunneling spectroscopy (CITS). Periodic density functional calculations simulating a polymer strand deposited on a HOPG surface are in agreement with the zig-zag structure indicated by experimental findings. Both the observed periodicity and the Zn-Zn distances can be reproduced in the simulations. Van der Waals interactions were found to play a major role for the geometry of the isolated polymer strand, for the adsorption geometry on HOPG, as well as for the adsorption energy.
Keywords: atomic force microscopy; coordination polymers; ligand design; scanning tunneling microscopy; zinc

N,N,O ligands based on triazoles and transition metal complexes thereof - Hübner, Eike; Fischer, Nina; Heinemann, Frank Wilhelm; Mitra, Utpal; Dremov, Viatcheslav; Müller, Paul; Burzlaff, Nicolai (European Journal of Inorganic Chemistry, 2010)
The reaction of 2H-benzotriazole (1) with dichloroacetic acid leads to the symmetric bis(2H-benzotriazol-2-yl)methane (2c) in 40 % yield. Deprotonation of 2c at the bridging methylene group and subsequent carboxylation with CO yielded the new tripodal N,N,O ligand bis(2H-benzotriazol-2-yl) acetic acid Hbbta (3). The sterically less demanding sodium bis(1H- ,4-triazol-1-yl)propionate Na[btp] (5) was obtained by saponification of methyl -bis(1H- ,4-triazol-1-yl)propionate (4). The heteroscorpionate hgand 3 viras treated with [MnBr(CO) ] and [RuCl (PPh J ] to form the manganese tricarbonyl complex [Mn(bbta)(CO) ] (6) and the air stable ruthenium complex [Ru(bbta)Cl(PPh ) ] (7). DFT calculations and the IR spectra of the carbonyl complex 6 reveal ligand 3 to be a less electron-donating ligand compared to the Ms(1Hpyrazol-1-yl)acetic acid Hbpza. In case of the 1H- ,4-triazole-based ligand 5 formation of coordination polymers were observed as proven by the synthesis of [Zn(btp)2∞ (8) and [Mn(btp) ]∞ (9). Polymer 8 crystallises in linear chains of zinc atoms bridged by two molecules of ligand 5 each. These polymer chains show an interesting π-stacking interaction between uncoordinated triazole residues of the ligands. Deposition of the coordination polymer on highly ordered pyrolytic graphite (HOPG) was successful and was analysed by scanning tunnelling microscopy (STM). Reaction of Na[btp] (5) with MnSO -H O resulted in a metal organic framework (MOF) [Mn(Mp) ]∞ (9). © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Trans-1,2-bis(N-methylimidazol-2-yl)ethylene: Towards building blocks for 2D fabrics and MML-type 1D molecular strands - Fischer, Nina; Alam, Sahabul; Jum'H, Inshad; Stocker, Michael; Fritsch, Nico; Dremov, Viatcheslav; Heinemann, Frank Wilhelm; Burzlaff, Nicolai; Müller, Paul (Chemistry - A European Journal, 2011)
Find the thread: Copper acetate and trans-bis(N-methylimidazol-2-yl) ethylene-derived 1D coordination polymers were investigated on mica and highly oriented pyrolytic graphite (HOPG) substrates by using AFM/STM. On HOPG, single isolated strands were mapped by STM and their electronic properties were subsequently characterized by current imaging tunneling spectroscopy. On mica the material shows a tendency to form bundles of strands. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.